Our constitution - Shad Saleem Faruqi (Thomson Reuters, 2019)
This book has been specially written to provide a good and clear understanding of the Malaysian Federal Constitution to all. Prepared by Malaysia's acknowledged constitutional law expert, Shad Saleem Faruqi, it is a book full of valuable information on the intricacies of the workings of Malaysia's supreme law. Drawing from his extensive knowledge of the subject, the author has prepared a text that is comprehensive, yet easy-to-read. For those needing more in-depth sources, relevant case authorities and provisions of the Constitution have been provided. Divided into 9 Parts comprising a total of 36 chapters, this book explains important topics like the main characteristics of the Federal Constitution, separation of powers, fundamental liberties, citizenship, the Conference of Rulers, the Yang Di-Pertuan Agong, ministerial responsibility, the making of laws, the judiciary, the electoral process and the powers to combat subversion. It also looks at the pre-Merdeka ethnic compromises and considers the future of the Constitution. Containing a thoroughly enlightening and engaging account of the Constitution, this is a book which should be read by all Malaysians, young and old, to have an essential appreciation of the supreme law which formed this country and continues to provide the framework to secure its future prosperity.